Assessing Risk Factors of Pneumonia among Adults at Ibn-Sina in Mosul City - Sana Thanoon Ahmed (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: the aim of the study to assess the most common risk factors of pneumonia at adult and find the socio-demographic characteristics of sample. Methodology: the study performed at Ibn-Sina teaching hospital (intensive care unit) and out patient in the same hospital period of (15 ) November (2006) till (1ا٤) February (2007).The sample of the study includes (65) patients with pneumonia for different underlying causes who were attending Ibn-Sina teaching hospital age range (59-68) years is the highest level and is the most common risk factor for pneumonia. Results: the results of the study most patients’ hospital acquired-pneumonia from contamination during administration to hospital but community acquired-pneumonia were difficult in swelling, bad cleaning of mouth and smoking. Recommendations: This study recommends providing pneumococcal pneumonia vaccine for adult those at risk for serious pneumonia and should be revaccinated every six years.